vec-len-via-list and length-toList are the same
[~helmut/bidiragda.git] / LiftGet.agda
1 module LiftGet where
2
3 open import Data.Unit using (⊤ ; tt)
4 open import Data.Nat using (ℕ ; suc)
5 open import Data.Vec using (Vec ; toList ; fromList) renaming ([] to []V ; _∷_ to _∷V_)
6 open import Data.List using (List ; [] ; _∷_ ; length ; replicate ; map)
7 open import Data.List.Properties using (length-map)
8 open import Data.Product using (∃ ; _,_ ; proj₁ ; proj₂)
9 open import Function using (_∘_ ; flip ; const)
10 open import Relation.Binary.Core using (_≡_)
11 open import Relation.Binary.PropositionalEquality using (_≗_ ; sym ; cong ; refl ; subst ; trans ; proof-irrelevance)
12 open Relation.Binary.PropositionalEquality.≡-Reasoning using (begin_ ; _≡⟨_⟩_ ; _∎)
13
14 get-type : Set₁
15 get-type = {A : Set} → List A → List A
16
17 getV-type : (ℕ → ℕ) → Set₁
18 getV-type getlen = {A : Set} {n : ℕ} → Vec A n → Vec A (getlen n)
19
20 getVec-to-getList : {getlen : ℕ → ℕ} → (getV-type getlen) → get-type
21 getVec-to-getList get = toList ∘ get ∘ fromList
22
23 getList-to-getlen : get-type → ℕ → ℕ
24 getList-to-getlen get = length ∘ get ∘ flip replicate tt
25
26 postulate
27   free-theorem-list-list : {β γ : Set} → (get : get-type) → (f : β → γ) → get ∘ map f ≗ map f ∘ get
28
29 replicate-length : {A : Set} → (l : List A) → map (const tt) l ≡ replicate (length l) tt
30 replicate-length [] = refl
31 replicate-length (_ ∷ l) = cong (_∷_ tt) (replicate-length l)
32
33 getList-length : (get : get-type) → {B : Set} → (l : List B) → length (get l) ≡ getList-to-getlen get (length l)
34 getList-length get l = begin
35   length (get l)
36     ≡⟨ sym (length-map (const tt) (get l)) ⟩
37   length (map (const tt) (get l))
38     ≡⟨ cong length (sym (free-theorem-list-list get (const tt) l)) ⟩
39   length (get (map (const tt) l))
40     ≡⟨ cong (length ∘ get) (replicate-length l) ⟩
41   length (get (replicate (length l) tt)) ∎
42
43 length-toList : {A : Set} {n : ℕ} → (v : Vec A n) → length (toList v) ≡ n
44 length-toList []V = refl
45 length-toList (x ∷V xs) = cong suc (length-toList xs) 
46
47 toList-fromList : {A : Set} → (l : List A) → toList (fromList l) ≡ l
48 toList-fromList []       = refl
49 toList-fromList (x ∷ xs) = cong (_∷_ x) (toList-fromList xs)
50
51 toList-subst : {A : Set} → {n m : ℕ} (v : Vec A n) → (p : n ≡ m) → toList (subst (Vec A) p v) ≡ toList v
52 toList-subst v refl = refl
53
54 getList-to-getVec-length-property : (get : get-type) → {C : Set} → {m : ℕ} → (v : Vec C m) → length (get (toList v)) ≡ length (get (replicate m tt))
55 getList-to-getVec-length-property get {_} {m} v = begin
56     length (get (toList v))
57       ≡⟨ getList-length get (toList v) ⟩
58     length (get (replicate (length (toList v)) tt))
59       ≡⟨ cong (length ∘ get ∘ flip replicate tt) (length-toList v) ⟩
60     length (get (replicate m tt)) ∎
61
62 getList-to-getVec : get-type → ∃ λ (getlen : ℕ → ℕ) → (getV-type getlen)
63 getList-to-getVec get = getlen , get'
64   where getlen : ℕ → ℕ
65         getlen = getList-to-getlen get
66         get' : {C : Set} {m : ℕ} → Vec C m → Vec C (getlen m)
67         get' {C} v = subst (Vec C) (getList-to-getVec-length-property get v) (fromList (get (toList v)))
68
69 subst-subst : {A : Set} (T : A → Set) {a b c : A} → (p : a ≡ b) → (p' : b ≡ c) → (x : T a)→ subst T p' (subst T p x) ≡ subst T (trans p p') x
70 subst-subst T refl p' x = refl
71
72 subst-fromList : {A : Set} {x y : List A} → (p : y ≡ x) → subst (Vec A) (cong length p) (fromList y) ≡ fromList x
73 subst-fromList refl = refl
74
75 get-commut-1 : (get : get-type) {A : Set} → (l : List A) → fromList (get l) ≡ subst (Vec A) (sym (getList-length get l)) (proj₂ (getList-to-getVec get) (fromList l))
76 get-commut-1 get {A} l = begin
77   fromList (get l)
78     ≡⟨ sym (subst-fromList (cong get (toList-fromList l))) ⟩
79   subst (Vec A) (cong length (cong get (toList-fromList l))) (fromList (get (toList (fromList l))))
80     ≡⟨ cong (flip (subst (Vec A)) (fromList (get (toList (fromList l))))) (proof-irrelevance (cong length (cong get (toList-fromList l))) (trans p p')) ⟩
81   subst (Vec A) (trans p p') (fromList (get (toList (fromList l))))
82     ≡⟨ sym (subst-subst (Vec A) p p' (fromList (get (toList (fromList l))))) ⟩
83   subst (Vec A) p' (subst (Vec A) p (fromList (get (toList (fromList l)))))
84     ≡⟨ refl ⟩
85   subst (Vec A) p' (proj₂ (getList-to-getVec get) (fromList l)) ∎
86     where p : length (get (toList (fromList l))) ≡ length (get (replicate (length l) tt))
87           p = getList-to-getVec-length-property get (fromList l)
88           p' : length (get (replicate (length l) tt)) ≡ length (get l)
89           p' = sym (getList-length get l)
90
91 get-trafo-1 : (get : get-type) → {B : Set} → getVec-to-getList (proj₂ (getList-to-getVec get)) {B} ≗ get {B}
92 get-trafo-1 get {B} l = begin
93   getVec-to-getList (proj₂ (getList-to-getVec get)) l
94     ≡⟨ refl ⟩
95   toList (proj₂ (getList-to-getVec get) (fromList l))
96     ≡⟨ refl ⟩
97   toList (subst (Vec B) (getList-to-getVec-length-property get (fromList l)) (fromList (get (toList (fromList l)))))
98     ≡⟨ toList-subst (fromList (get (toList (fromList l)))) (getList-to-getVec-length-property get (fromList l)) ⟩
99   toList (fromList (get (toList (fromList l))))
100     ≡⟨ toList-fromList (get (toList (fromList l))) ⟩
101   get (toList (fromList l))
102     ≡⟨ cong get (toList-fromList l) ⟩
103   get l ∎
104
105 vec-len : {A : Set} {n : ℕ} → Vec A n → ℕ
106 vec-len {_} {n} _ = n
107
108 length-replicate : {A : Set} {a : A} → (n : ℕ) → length (replicate n a) ≡ n
109 length-replicate 0       = refl
110 length-replicate (suc n) = cong suc (length-replicate n)
111
112 ∷-subst : {A : Set} {n m : ℕ} → (x : A) → (xs : Vec A n) → (p : n ≡ m) → x ∷V subst (Vec A) p xs ≡ subst (Vec A) (cong suc p) (x ∷V xs)
113 ∷-subst x xs refl = refl
114
115 fromList-toList : {A : Set} {n : ℕ} → (v : Vec A n) → fromList (toList v) ≡ subst (Vec A) (sym (length-toList v)) v
116 fromList-toList     []V       = refl
117 fromList-toList {A} (x ∷V xs) = begin
118   x ∷V fromList (toList xs)
119     ≡⟨ cong (_∷V_ x) (fromList-toList xs) ⟩
120   x ∷V subst (Vec A) (sym (length-toList xs)) xs
121     ≡⟨ ∷-subst x xs (sym (length-toList xs)) ⟩
122   subst (Vec A) (cong suc (sym (length-toList xs))) (x ∷V xs)
123     ≡⟨ cong (λ p →  subst (Vec A) p (x ∷V xs)) (proof-irrelevance (cong suc (sym (length-toList xs))) (sym (cong suc (length-toList xs)))) ⟩
124   subst (Vec A) (sym (length-toList (x ∷V xs))) (x ∷V xs) ∎
125
126 subst-cong : {A : Set} (T : A → Set) {a b : A} → (f' : A → A) → (f : {c : A} → T c → T (f' c)) → (x : T a) → (p : a ≡ b) → f (subst T p x) ≡ subst T (cong f' p) (f x)
127 subst-cong T f' f x refl = refl
128
129 get-commut-2 : (getlen : ℕ → ℕ) → (get : getV-type getlen) → {B : Set} {n : ℕ} → (toList ∘ get {B} {n}) ≗ (getVec-to-getList get) ∘ toList
130 get-commut-2 getlen get {B} v = begin
131   toList (get v)
132     ≡⟨ sym (toList-subst (get v) (cong getlen (sym (length-toList v)))) ⟩
133   toList (subst (Vec B) (cong getlen (sym (length-toList v))) (get v))
134     ≡⟨ cong toList (sym (subst-cong (Vec B) getlen get v (sym (length-toList v)))) ⟩
135   toList (get (subst (Vec B) (sym (length-toList v)) v))
136     ≡⟨ cong (toList ∘ get) (sym (fromList-toList v)) ⟩
137   toList (get (fromList (toList v))) ∎
138
139 get-trafo-2-getlen : (getlen : ℕ → ℕ) → (get : getV-type getlen) → proj₁ (getList-to-getVec (getVec-to-getList get)) ≗ getlen
140 get-trafo-2-getlen getlen get n = begin
141   proj₁ (getList-to-getVec (getVec-to-getList get)) n
142     ≡⟨ refl ⟩
143   length (toList (get (fromList (replicate n tt))))
144     ≡⟨ length-toList (get (fromList (replicate n tt))) ⟩
145   vec-len (get (fromList (replicate n tt)))
146     ≡⟨ cong getlen (length-replicate n) ⟩
147   getlen n ∎
148
149 getVec-getlen : {getlen₁ getlen₂ : ℕ → ℕ} → (get : getV-type getlen₁) → getlen₁ ≗ getlen₂ → getV-type getlen₂
150 getVec-getlen get p {B} {n} v = subst (Vec B) (p n) (get v)
151
152 get-trafo-2-get : (getlen : ℕ → ℕ) → (get : getV-type getlen) → {B : Set} {n : ℕ} → proj₂ (getList-to-getVec (getVec-to-getList get)) {B} {n} ≗ getVec-getlen get (sym ∘ (get-trafo-2-getlen getlen get))
153 get-trafo-2-get getlen get {B} {n} v = begin
154   proj₂ (getList-to-getVec (getVec-to-getList get)) v
155     ≡⟨ refl ⟩
156   subst (Vec B) p (fromList (toList (get (fromList (toList v)))))
157     ≡⟨ cong (subst (Vec B) p) (fromList-toList (get (fromList (toList v)))) ⟩
158   subst (Vec B) p (subst (Vec B) p' (get (fromList (toList v))))
159     ≡⟨ subst-subst (Vec B) p' p (get (fromList (toList v))) ⟩
160   subst (Vec B) (trans p' p) (get (fromList (toList v)))
161     ≡⟨ cong (subst (Vec B) (trans p' p) ∘ get) (fromList-toList v) ⟩
162   subst (Vec B) (trans p' p) (get (subst (Vec B) (sym (length-toList v)) v))
163     ≡⟨ cong (subst (Vec B) (trans p' p)) (subst-cong (Vec B) getlen get v (sym (length-toList v))) ⟩
164   subst (Vec B) (trans p' p) (subst (Vec B) (cong getlen (sym (length-toList v))) (get v))
165     ≡⟨ subst-subst (Vec B) (cong getlen (sym (length-toList v))) (trans p' p) (get v) ⟩
166   subst (Vec B) (trans (cong getlen (sym (length-toList v))) (trans p' p)) (get v)
167     ≡⟨ cong (flip (subst (Vec B)) (get v)) (proof-irrelevance (trans (cong getlen (sym (length-toList v))) (trans p' p)) p'') ⟩
168   subst (Vec B) p'' (get v)
169     ≡⟨ refl ⟩
170   getVec-getlen get (sym ∘ (get-trafo-2-getlen getlen get)) v ∎
171     where n' : ℕ
172           n' = length (toList (get (fromList (replicate n tt))))
173           p : length (toList (get (fromList (toList v)))) ≡ n'
174           p = getList-to-getVec-length-property (getVec-to-getList get) v
175           p' : getlen (length (toList v)) ≡ length (toList (get (fromList (toList v))))
176           p' = sym (length-toList (get (fromList (toList v))))
177           p'' : getlen n ≡ n'
178           p'' = sym (get-trafo-2-getlen getlen get (vec-len v))